Insulin Resistance Promotes Early Atherosclerosis via Increased Proinflammatory Proteins and Oxidative Stress in Fructose-Fed ApoE-KO Mice - Cannizzo, Beatriz (2012)
High fructose intake induces an insulin resistance state associated with metabolic syndrome (MS). The effect of vascular inflammation in this model is not completely addressed. The aim of this study was to evaluate vascular remodeling, inflammatory and oxidative stress markers, and atheroma development in high-fructose diet-induced insulin resistance of ApoE-deficient mice (ApoE-KO). Mice were fed with either a normal chow or a 10% w/v fructose (HF) in drinking water over a period of 8 weeks. Thereafter, plasma metabolic parameters, vascular remodeling, atheroma lesion size, inflammatory markers, and NAD(P)H oxidase activity in the arteries were determined. HF diet induced a marked increase in plasma glucose, insulin, and triglycerides in ApoE-KO mice, provoked vascular remodeling, enhanced expression of vascular cell-adhesion molecule-1 (VCAM-1) and matrix metalloprotease 9 (MMP-9) and enlarged herosclerotic lesion in aortic and carotid arteries. NAD(P)H oxidase activity was enhanced by fructose intake, and this effect was attenuated by tempol, a superoxide dismutase mimetic, and losartan, an Angiotensin II receptor antagonist. Our study results show that high-fructose-induced insulin resistance promotes a proinflammatory and prooxidant state which accelerates atherosclerotic plaque formation in ApoE-KO mice